SEKSUALITAS PEREMPUAN DALAM ISLAM - Munfarida, Elya (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2010)
Religion exists to make changes in the existing social order. With a foothold on tawhid (oneness of God), and affirms thedoctrine of universal human equality. This doctrine of tawhid in turn has implications for the transformation of various forms of social practicesthat subordinate and exploit the other party. On this basis, women's issues, including aspects of sexuality, is also undergoing atransformation. With the doctrine of equality, both men and women can obtain their rights as human beings as equals. Each side has aposition as a partner and therefore entitled to recreational sexuality. Various discourse in Islamic thought who presume to eliminate the rightof either party, especially with the tendency to subordinate such party, of course contrary to the spirit of equality contained in the doctrine ofmonotheism